Neural stem cell lineage-specific cannabinoid type-1 receptor regulates neurogenesis and plasticity in the adult mouse hippocampus. (11th October 2018) - Zimmermann, Tina; Maroso, Mattia; Beer, Annika; Baddenhausen, Sarah; Ludewig, Susann; Fan, Wenqiang; Vennin, Constance; Loch, Sebastian; Berninger, Benedikt; Hofmann, Clementine; Korte, Martin; Soltesz, Ivan; et al.
Abstract: Neural stem cells (NSCs) in the adult mouse hippocampus occur in a specific neurogenic niche, where a multitude of extracellular signaling molecules converges to regulate NSC proliferation as well as fate and functional integration. However, the underlying mechanisms how NSCs react to extrinsic signals and convert them to intracellular responses still remains elusive. NSCs contain a functional endocannabinoid system, including the cannabinoid type-1 receptor (CB1). To decipher whether CB1 regulates adult neurogenesis directly or indirectly in vivo, we performed NSC-specific conditional inactivation of CB1 by using triple-transgenic mice. Here, we show that lack of CB1 in NSCs is sufficient to decrease proliferation of the stem cell pool, which consequently leads to a reduction in the number of newborn neurons. Furthermore, neuronal differentiation was compromised at the level of dendritic maturation pointing towards a postsynaptic role of CB1 in vivo . Deteriorated neurogenesis in NSC-specific CB1 knock-outs additionally resulted in reduced long-term potentiation in the hippocampal formation. The observed cellular and physiological alterations led to decreased short-term spatial memory and increased depression-like behavior. These results demonstrate that CB1 expressed in NSCs and their progeny controls neurogenesis in adult mice to regulate the NSC stem cell pool, dendritic morphology, activity-dependent plasticity, and behavior.